2000
DOI: 10.1007/bf02932005
|View full text |Cite
|
Sign up to set email alerts
|

Lower eicosapentaenoic acid and higher arachidonic acid levels in Sera of young adults in the Netherlands than in Japan

Abstract: To survey risk factors in coronary heart disease, we compared serum fatty acid composition and lipids for university students in Japan (33 males and 29 females) and in the Netherlands (20 males and 19 females). No significant differences were found between the mean levels of cholesterol (Chol) and triglycerides (TG) between the subjects in the two countries. The mean levels of polyunsaturated fatty acid (PUFA), monounsaturated fatty acid (MUFA) and saturated fatty acid (SFA) of Japanese students were similar t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Furthermore, the large cardiovascular trials have demonstrated clinical benefits to increasing the dose of n-3 PUFAs in the diet 13 . Based on the concentration of PUFAs in human serum 51 , we would hypothesize that the levels used in this study should be looked at as a pharmacological effect of a physiological dose, which correlates with evidence from the literature.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Furthermore, the large cardiovascular trials have demonstrated clinical benefits to increasing the dose of n-3 PUFAs in the diet 13 . Based on the concentration of PUFAs in human serum 51 , we would hypothesize that the levels used in this study should be looked at as a pharmacological effect of a physiological dose, which correlates with evidence from the literature.…”
Section: Discussionsupporting
confidence: 66%
“…The best concentration for cellular response has been in the 5μg/ml range for both types of FAs for all cell types. Furthermore, this concentration remains within human physiological range, estimated to be on average 16.1 mg/100ml in Japanese male and 21.1 mg/100ml in Dutch males sera for AA, and 3.7 mg/100ml and 1.0 mg/100ml for EPA in Japanese and Dutch sera, respectively 51 . These factors, as well as general limitations when comparing in vitro to in vivo studies restrict the direct applicability to clinical settings.…”
Section: Discussionmentioning
confidence: 63%